Cognitive Safety and Overall Tolerability of Imidafenacin in Clinical Use: A Long‐Term, Open‐Label, Post‐Marketing Surveillance Study. Issue 3 (28th July 2014) - SAKAKIBARA, Ryuji; HAMANO, Hitoshi; YAGI, Hiromitsu
<x xml:space="preserve">Abstract</x> Objectives To assess the effect of imidafenacin on cognitive function, including the conversion rate of mild cognitive impairment (MCI) to dementia, in a period of one year. Methods Patients newly administered imidafenacin to treat overactive bladder (OAB), including those who had MCI or dementia, were surveyed across Japan (cognitive safety analysis set [CSAS]), on all of whom we performed the Mini‐Mental State Examination (MMSE) at baseline, 24‐ and 48‐weeks after treatment. From CSAS, we extracted well described cases of OAB change as well as drug‐related adverse events of dry mouth etc. (efficacy analysis set [EAS]). From CSAS, we extracted MCI cases (MCI set [MCIS]) to analyze the conversion rate of MCI to dementia. MCI is defined by exclusion of normal individual and apparent dementia. Results The cognitive safety analysis set comprised 187 patients who were collected from 51 medical institutions, and no significant decrease was noted in the MMSE scores in the patients during follow‐up. EAS comprised 176 patients. In this group, drug‐related adverse events such as dry mouth were reported in 15 (8.5%). MCIS comprised 145 patients. In this group, the annual conversion rate of MCI to dementia was 3.6%, and this rate did not exceed those reported in past epidemiological studies (6.8–16.1% per year). Conclusions The present findings suggest that imidafenacin can be used safely for cognitively vulnerable patients with OAB.